Analysis of the Effects of Learning Patterns and Self-Regulated Learning on Numerical Methods Learning Outcomes among Informatics Engineering Students - Silvana Samaray (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2026)
Achieving optimal learning outcomes in Numerical Methods courses among Informatics Engineering students remains hindered by various academic obstacles. This study aims to investigate the extent to which study patterns and levels of Self-Regulated Learning influence the academic achievement in Numerical Methods of Informatics Engineering students. Utilizing a quantitative correlational design, data were gathered from 50 participants serving as the research sample. The research instruments comprised Likert-scale questionnaires to measure study patterns and SRL, supplemented by documentation of students' academic records. Data analysis was conducted using SPSS software through Pearson correlation and multiple linear regression tests. The findings confirm that study patterns maintain a positive and significant correlation with learning outcomes (r = 0,351; p = 0,013). Similarly, Self-Regulated Learning demonstrates a positive and significant correlation with academic achievement (r = 0,598; p = 0,000). Simultaneously, both variables exert a significant impact, contributing 60.1% (coefficient of determination) to learning outcomes. Regression analysis reveals that Self-Regulated Learning possesses a more substantial influence (? = 0,708) compared to the study pattern variable (? = 0,505). This research highlights the critical importance of developing students' Self-Regulated Learning and study patterns to enhance academic performance, particularly within the context of Numerical Methods instruction.